Formation agent and preparation method and application thereof
By using a forming agent composed of phosphoric acid, nitric acid, zinc dihydrogen phosphate, nickel salt, manganese salt, zinc salt, composite organic acid and solvent, a dense protective film layer is formed at low temperature, which solves the problem of poor corrosion resistance of the forming agent at low temperature and achieves good corrosion resistance and bonding strength.
Patent Information
- Application Number
- CN202510736062.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-04
- Publication Date
- 2025-10-10
AI Technical Summary
When existing chemical conversion agents are used to treat metal surfaces at low temperatures, the film layer formed has poor corrosion resistance, and the low-temperature treatment time is long and the cost is high.
A chemical agent composed of phosphoric acid, nitric acid, zinc dihydrogen phosphate, nickel salt, manganese salt, zinc salt, composite organic acid and solvent is used to form a dense protective film layer at low temperature, combined with nano lanthanum nitrate to improve corrosion resistance.
A dense protective film layer is formed at low temperature, which improves the corrosion resistance of the metal surface and combines with the electrophoretic paint film coating to extend the service life of the metal products.
Smart Images

Figure BDA0005433324790000041 
Figure BDA0005433324790000051
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal surface treatment, and in particular relates to a forming agent and a preparation method and application thereof. Background Art
[0002] Chemical formation agents are primarily used for metal surface treatment to improve the metal's corrosion resistance and wear resistance. Existing chemical formation agents are used in three different metal surface treatment processes: high temperature, medium temperature, and low temperature. High-temperature treatments are highly polluting and energy-intensive, and the chemical formation agent easily decomposes, resulting in coarse grains in the film formed on the metal surface. Medium-temperature treatments produce films with poor quality stability. Low-temperature (e.g., room temperature) treatments, however, offer relatively good chemical stability and lower costs. However, low-temperature treatments require a long time and result in poor corrosion resistance in the resulting film.
[0003] Therefore, there is an urgent need to provide a new chemical forming agent that can not only treat metals at low temperatures, but also form a film layer on the metal surface with good corrosion resistance. Summary of the Invention
[0004] The present invention aims to address at least one of the technical problems existing in the aforementioned prior art. To this end, the present invention provides a forming agent, a preparation method, and applications thereof. The forming agent described herein is a low-temperature forming agent that, under low-temperature conditions (e.g., 15-35°C), can form a dense protective film layer on a metal surface, exhibiting excellent corrosion resistance. When an electrophoretic paint film is applied to the surface of the protective film layer, the protective film layer exhibits excellent bonding strength with the paint film coating.
[0005] A first aspect of the present invention provides a formation agent.
[0006] Specifically, a forming agent includes phosphoric acid, nitric acid, zinc dihydrogen phosphate, nickel salt, manganese salt, zinc salt, composite organic acid and solvent;
[0007] The composite organic acid includes citric acid, tartaric acid and pyromellitic acid;
[0008] The zinc salt does not include zinc dihydrogen phosphate.
[0009] Preferably, in the composite organic acid, the weight ratio of citric acid, tartaric acid and pyromellitic acid is 1:(1-3):(0.1-0.5), more preferably 1:(1.5-2.5):(0.2-0.4).
[0010] Preferably, the nickel salt includes nickel nitrate or nickel sulfate.
[0011] Preferably, the manganese salt comprises manganese nitrate.
[0012] Preferably, the zinc salt comprises zinc nitrate or zinc sulfate.
[0013] Preferably, the solvent includes water and / or ethanol, more preferably deionized water.
[0014] Preferably, the formation agent comprises, by weight, 18-32 parts of phosphoric acid, 1-6 parts of nitric acid, 1-12 parts of zinc dihydrogen phosphate, 0.1-5.5 parts of nickel salt, 4-11 parts of manganese salt, 4.5-11 parts of zinc salt, 0.5-5 parts of composite organic acid, and 20-50 parts of solvent; in the composite organic acid, the weight ratio of citric acid, tartaric acid, and pyromellitic acid is 1:(1-3):(0.1-0.5); Further preferably, the formation agent comprises, by weight, 20-30 parts of phosphoric acid, 1-5 parts of nitric acid, 1-10 parts of zinc dihydrogen phosphate, 0.1-5 parts of nickel salt, 5-10 parts of manganese salt, 5-10 parts of zinc salt, 1-3 parts of composite organic acid, and 20-50 parts of solvent; in the composite organic acid, the weight ratio of citric acid, tartaric acid, and pyromellitic acid is 1:(1.5-2.5):(0.2-0.4).
[0015] Preferably, the formation agent further comprises nano-lanthanum nitrate. For example, adding 0.05-0.3 parts of nano-lanthanum nitrate helps to further improve the corrosion resistance of the protective film layer formed by the formation agent on the metal surface.
[0016] Preferably, the formation agent comprises, by weight, 20-30 parts of phosphoric acid, 1-5 parts of nitric acid, 1-10 parts of zinc dihydrogen phosphate, 0.1-5 parts of nickel salt, 5-10 parts of manganese salt, 5-10 parts of zinc salt, 1-3 parts of composite organic acid, 0.05-0.3 parts of nano-lanthanum nitrate and 20-50 parts of solvent; in the composite organic acid, the weight ratio of citric acid, tartaric acid and pyromellitic acid is 1:(1.5-2.5):(0.2-0.4).
[0017] A second aspect of the present invention provides a method for preparing a formation agent.
[0018] Specifically, a method for preparing a formation agent comprises the following steps:
[0019] The components are mixed to prepare the forming agent.
[0020] Preferably, the preparation method comprises the following steps:
[0021] Phosphoric acid, nitric acid, composite organic acid and part of solvent are mixed, zinc salt is added, mixed and then remaining components are added to prepare the forming agent.
[0022] The third aspect of the present invention provides a use of a formation agent.
[0023] A metal product comprises a metal substrate and a protective film layer attached to the surface of the metal substrate, wherein the protective film layer is formed by the above-mentioned chemical forming agent.
[0024] Preferably, the metal substrate comprises any one of steel, zinc, aluminum alloy, magnesium alloy.
[0025] Preferably, the thickness of the protective film layer on the surface of the metal substrate is 1.0-3.5 g / m 2 , and more preferably 2.0-3.5 g / m 2 .
[0026] Preferably, an electrophoretic paint film coating is further attached to the protective film layer.
[0027] Compared with the prior art, the present application has the following advantages:
[0028] (1) The chemical conversion agent comprises phosphoric acid, nitric acid, zinc dihydrogen phosphate, nickel salt, manganese salt, zinc salt, complex organic acid, and solvent; the complex organic acid comprises citric acid, tartaric acid, and pyromellitic acid. Through the use of each component, especially the combination of zinc dihydrogen phosphate, nickel salt, manganese salt, zinc salt, and complex organic acid, the complex organic acid in the present application is obtained by the combination of specific aliphatic polybasic organic acid and aromatic polybasic organic acid, so that the chemical conversion agent can form a dense protective film layer on the metal surface at low temperature, thereby providing good protection to the metal and improving the corrosion resistance.
[0029] (2) The chemical conversion agent comprises a small amount of nano lanthanum nitrate. The introduction of a small amount of nano lanthanum nitrate of rare earth class, the interaction of lanthanum ions with other metal ions (nickel, manganese, zinc) and the network structure formed by the complex organic acid makes the protective film layer more dense, thereby further improving the corrosion resistance of the protective film layer formed by the chemical conversion agent on the metal surface. DETAILED DESCRIPTION
[0030] In order to make the skilled person in the art more clearly understand the technical solutions of the present application, the following examples are given for illustration. It should be pointed out that the following examples do not limit the scope of protection required by the present application.
[0031] The raw materials, reagents or devices used in the following examples are commercially available or can be obtained by known methods unless otherwise specified.
[0032] Example 1
[0033] A chemical conversion agent comprises, by weight fraction, 25 parts of phosphoric acid, 3 parts of nitric acid, 5 parts of zinc dihydrogen phosphate, 2.5 parts of nickel nitrate, 5 parts of manganese nitrate, 5 parts of zinc nitrate, 1.5 parts of complex organic acid, and 45 parts of deionized water, 5 parts of ethanol.
[0034] In the complex organic acid, the weight ratio of citric acid, tartaric acid, and pyromellitic acid is 1:1.5:0.2.
[0035] A method for preparing a forming agent comprises the following steps:
[0036] Phosphoric acid, nitric acid, and a composite organic acid, as well as half of the deionized water and all of the ethanol, were mixed for 30 minutes at a stirring speed of 50 rpm, and then zinc nitrate was added and the mixture was mixed for 10 minutes. The remaining components were then added to prepare a forming agent.
[0037] Example 2
[0038] A forming agent, comprising, by weight, 20 parts of phosphoric acid, 2 parts of nitric acid, 8 parts of zinc dihydrogen phosphate, 1 part of nickel nitrate, 5.5 parts of manganese nitrate, 4.5 parts of zinc nitrate, 0.8 parts of a composite organic acid, 40 parts of deionized water, and 5 parts of ethanol;
[0039] In the composite organic acid, the weight ratio of citric acid, tartaric acid and pyromellitic acid is 1:2:0.1.
[0040] A method for preparing a forming agent comprises the following steps:
[0041] Phosphoric acid, nitric acid, and a composite organic acid, as well as half of the deionized water and all of the ethanol, were mixed for 30 minutes at a stirring speed of 50 rpm, and then zinc nitrate was added and the mixture was mixed for 10 minutes. The remaining components were then added to prepare a forming agent.
[0042] Example 3
[0043] A forming agent, comprising, by weight, 25 parts of phosphoric acid, 3 parts of nitric acid, 5 parts of zinc dihydrogen phosphate, 2.5 parts of nickel nitrate, 5 parts of manganese nitrate, 5 parts of zinc nitrate, 1.5 parts of a composite organic acid, 45 parts of deionized water, 5 parts of ethanol, and 0.1 part of nano-lanthanum nitrate;
[0044] In the composite organic acid, the weight ratio of citric acid, tartaric acid and pyromellitic acid is 1:1.5:0.2.
[0045] A method for preparing a forming agent comprises the following steps:
[0046] Phosphoric acid, nitric acid, and a composite organic acid, as well as half of the deionized water and all of the ethanol, were mixed for 30 minutes at a stirring speed of 50 rpm, and then zinc nitrate was added and the mixture was mixed for 10 minutes. The remaining components were then added to prepare a forming agent.
[0047] Comparative Example 1
[0048] Compared with Example 1, the only difference of Comparative Example 1 is that zinc dihydrogen phosphate is not contained, and other components and preparation process are the same as those of Example 1.
[0049] Comparative Example 2
[0050] Compared with Example 1, the only difference of Comparative Example 2 is that nickel nitrate is not contained, and other components and preparation process are the same as those of Example 1.
[0051] Comparative Example 3
[0052] Compared with Example 1, the only difference of Comparative Example 3 is that citric acid and tartaric acid are replaced by equal amounts of oxalic acid, and other components and preparation process are the same as those of Example 1.
[0053] Comparative Example 4
[0054] Compared with Example 1, the only difference of Comparative Example 4 is that an equal amount of salicylic acid is used instead of pyromellitic acid, and the other components and preparation process are the same as those of Example 1.
[0055] Product effect testing
[0056] 1. Copper sulfate drip test
[0057] The conversion agents prepared in Example 1 and Comparative Examples 1 and 3-4 were taken, respectively, and a clean cold-rolled steel sheet was immersed in the conversion agent. The mixture was incubated at 25°C for 5 minutes, then removed, washed with water, and dried to obtain a cold-rolled steel sheet with a protective film layer on its surface. The corrosion resistance of the cold-rolled steel sheet with a protective film layer was then tested using a conventional copper sulfate drop test (the copper sulfate drop test involves dropping a drop of copper sulfate test solution on the surface of the protective film layer while starting a stopwatch and observing the time it takes for the drop to change color from sky blue to light red to evaluate the corrosion resistance of the film layer). The results are shown in Table 1.
[0058] Table 1
[0059]
[0060] As can be seen from Table 1, the discoloration time of the examples of the present invention is significantly longer than that of the comparative examples, indicating that the protective film layer formed by the corresponding chemical formation agent of the examples has better corrosion resistance. As can be seen from Example 1 and Comparative Examples 3-4, the present invention is selective in its choice of composite organic acid. Only in the presence of the specific composite organic acid of the present invention does the film layer formed by the chemical formation agent have better density, better barrier properties, and thus better corrosion resistance.
[0061] 2. Neutral salt spray resistance test
[0062] Take the chemical conversion agents prepared in Example 1 and Comparative Examples 1, 3-4 above, respectively, immerse the cold-rolled steel sheet with a clean surface in the chemical conversion agent, keep it warm at 25°C for 5 minutes, take out the cold-rolled steel sheet (each Example or Comparative Example corresponds to 4 cold-rolled steel sheets), wash it with water, and dry it to obtain a cold-rolled steel sheet with a protective film layer on the surface, then electrophoretically apply the protective film layer to the surface, and then bake it at 175°C for 25-30 minutes to form a 17 μm thick electrophoretic paint film.
[0063] The test was carried out according to the method of GB / T9286-1998. An "X" scratch was made on the surface of the resin coating, and then the surface was placed in a neutral salt spray chamber for a 1000-hour neutral salt spray test. The test temperature was 47±2°C, the spray pressure was 120KPa, and the concentration of the sodium chloride solution was 50g / L. The cold-rolled steel sheet was taken out and attached to the "X" scratch surface with 3M tape. The 3M tape was then pulled apart. The width of the "X" scratch on one side was counted and the width was averaged (the wider the width of the "X" scratch on one side, the worse the surface corrosion resistance and the bonding strength between the resin coating and the protective film layer). The cold-rolled steel sheet was then placed in a neutral salt spray chamber for a 200-hour neutral salt spray test (i.e., a total of 1200 hours of neutral salt spray test were performed). The cold-rolled steel sheet was taken out and attached to the "X" scratch surface with 3M tape. The 3M tape was then pulled apart. The width of the "X" scratch on one side was counted and the width was averaged. The results are shown in Table 2.
[0064] Table 2
[0065]
[0066] As can be seen from Table 2, after 1000 hours of neutral salt spray test, the unilateral corrosion of the X scratch of Comparative Example 2 has reached 2.1 mm. After continuing the salt spray corrosion for 200 hours, the corrosion is aggravated and the unilateral corrosion expands to 4.3 mm.
[0067] The salt spray corrosion resistance of Comparative Examples 3-4 is also significantly worse than that of Example 1 and Example 3.
[0068] After 1000h of salt spray corrosion, the sample of Example 1 had no obvious corrosion on the surface, and the unilateral corrosion of the X scratch was only 0.6mm. After continuing to carry out salt spray corrosion for 200h, the unilateral corrosion of the X scratch expanded to 1.7mm. After 1000h of salt spray corrosion, the sample of Example 3 had no obvious corrosion on the surface, and the unilateral corrosion of the X scratch was 0.5mm. After continuing to carry out salt spray corrosion for 200h, the unilateral corrosion of the X scratch expanded to 1.5mm. It can be seen from this that the chemical forming agent prepared by the present invention has significantly improved salt spray corrosion resistance after forming a film layer on the metal surface in combination with the resin coating, which also shows that the chemical forming agent prepared by the present invention has good bonding strength between the protective film layer formed on the metal surface and the resin coating.
[0069] Generally, a 500-hour neutral salt spray test is equivalent to 10 years of outdoor use. This shows that metals treated with the chemical forming agent of the present invention have an outdoor service life of more than 10 years.
Claims
1. A formation agent, characterized in that Including phosphoric acid, nitric acid, zinc dihydrogen phosphate, nickel salts, manganese salts, zinc salts, complex organic acids and solvents; The composite organic acid includes citric acid, tartaric acid and pyromellitic acid; The zinc salt does not include zinc dihydrogen phosphate.
2. The formation agent according to claim 1, characterized in that In the composite organic acid, the weight ratio of citric acid, tartaric acid and pyromellitic acid is 1:(1-3):(0.1-0.5).
3. The formation agent according to claim 1, characterized in that The nickel salt includes nickel nitrate or nickel sulfate; and / or the manganese salt includes manganese nitrate.
4. The formation agent according to claim 1, characterized in that The zinc salt includes zinc nitrate or zinc sulfate; and / or the solvent includes water and / or ethanol.
5. The formation agent according to claim 1, characterized in that The formation agent comprises, by weight, 18-32 parts of phosphoric acid, 1-6 parts of nitric acid, 1-12 parts of zinc dihydrogen phosphate, 0.1-5.5 parts of nickel salt, 4-11 parts of manganese salt, 4.5-11 parts of zinc salt, 0.5-5 parts of composite organic acid, and 20-50 parts of solvent; in the composite organic acid, the weight ratio of citric acid, tartaric acid, and pyromellitic acid is 1:(1-3):(0.1-0.5).
6. The formation agent according to claim 1, characterized in that The formation agent also includes nano lanthanum nitrate.
7. The formation agent according to claim 6, characterized in that The formation agent comprises, by weight, 20-30 parts of phosphoric acid, 1-5 parts of nitric acid, 1-10 parts of zinc dihydrogen phosphate, 0.1-5 parts of nickel salt, 5-10 parts of manganese salt, 5-10 parts of zinc salt, 1-3 parts of composite organic acid, 0.05-0.3 parts of nano-lanthanum nitrate and 20-50 parts of solvent; in the composite organic acid, the weight ratio of citric acid, tartaric acid and pyromellitic acid is 1:(1.5-2.5):(0.2-0.4).
8. The method for preparing the formation agent according to any one of claims 1 to 7, characterized in that: The following steps are involved: The components are mixed to prepare the forming agent.
9. A metal product, characterized in that: It comprises a metal substrate and a protective film layer attached to the surface of the metal substrate, wherein the protective film layer is formed by the above-mentioned chemical forming agent.
10. The metal product according to claim 9, characterized in that The metal substrate includes any one of steel, zinc, aluminum alloy and magnesium alloy.